Neighbourhoods and neighbourliness in urban South Asia
1 online resource (1 volume)
Keywords: This volume examines urban South Asia through the ideas of neighbourhood and neighbourliness. With a focus on the affective socio-spatial and sensorial experiences of non-metropolitan, small and intermediate cities, the chapters in the volume look at neighbourhoods as akey to exploring the textures of urban life. Bringing together scholars from a variety of disciplines including sociology, anthropology, urban studies, planning, and social history, the book highlights urban heterogeneity and contemporary transformations in South Asia. It discusses the linkages between urban lived spaces and social life; memory, migration, and exile; and the city and its society through practices of everyday life in neighbourhoods. With studies from Sri Lanka, Nepal, Afghanistan, Bangladesh, and India, the volume addresses a wide range of issues pertaining to urban experiences in their regional specificities and in a broader context of the Global South. This book will be useful to scholars and researchers of urban sociology, anthropology, urban studies, planning and development, social history, political studies, cultural studies, geography, and South Asian studies. It will also interest practitioners and policymakers, architects, planners, civil society organisations, and thinktanks.